Livelihoods and Tourism: Capital Assets, Household Resiliency, and Subjective Wellbeing - Ian E. Munanura; Edwin Sabuhoro; Carter A. Hunt; Jim Ayorekire (Tourism and Hospitality, 2021)
Although a positive relationship between tourism and quality of life is the premise of using tourism to support biodiversity conservation, tourism scholars rarely assess the relationship between tourism and community livelihoods with rigorous empirical methods, even less so in African contexts. Focusing on communities in the Greater Virunga Landscape in Rwanda and Uganda, we conducted a household survey to acquire empirical data to test novel hypotheses about tourism’s influence on capital assets, household resiliency, and subjective wellbeing. Using inferential statistical analyses (e.g., analysis of variance, chi-square difference test, and independent sample t-tests), we compared the responses from 346 residents who have direct access to tourism livelihoods with responses collected from 224 residents not engaged in tourism. Contrary to expectations, our findings suggest that tourism may not lead to dramatic differences in access to capital assets. However, we did discover moderate influences on household resiliency and subjective wellbeing. These intangible and subjective wellbeing outcomes of tourism-based livelihood programs are challenging to assess empirically. Yet, they may be among some of the most important from a human development standpoint. As a first effort to integrate three theoretical frameworks that have, to date, seen limited application in tourism research, this study has opened the door to further work at the intersections of capital assets, family resilience, and wellbeing theories. In conclusion, we argue that incentivizing the protection of local environments through tourism must be extended to other forms of capital, while also considering more nuanced manifestations of intangible wellbeing outcomes. As such, this paper makes a significant empirical contribution to the ongoing theoretical and practical debates about the tourism-conservation relationship.